AIE/FRET-based versatile PEG-Pep-TPE/DOX nanoparticles for cancer therapy and real-time drug release monitoring. (28th November 2019) - Wang, Tian-Tian; Wei, Qi-Chun; Zhang, Zhen-Tao; Lin, Meng-Ting; Chen, Jie-Jian; Zhou, Yi; Guo, Ning-Ning; Zhong, Xin-Cheng; Xu, Wen-Hong; Liu, Zhan-Xiang; Han, Min; Gao, Jian-Qing
Abstract : Based on the biological significance of self-assembling peptides in program cell death, promoting proliferation of stem cells and suppressing immune responses, stimuli-responsive polypeptide nanoparticles have attracted more and more attention. Abstract : On account of the biological significance of self-assembling peptides in blocking the cellular mass exchange as well as impeding the formation for actin filaments resulting in program cell death, stimuli-responsive polypeptide nanoparticles have attracted more and more attention. In this work, we successfully fabricated doxorubicin-loaded polyethylene glycol-block-peptide (FFKY)-block-tetraphenylethylene (PEG-Pep-TPE/DOX) nanoparticles, where the aggregation-induced emission luminogens (AIEgen, TPE-CHO) can become a fluorescence resonance energy transfer (FRET) pair with the entrapped antitumor drug DOX to detect the release of drugs dynamically. This is the first successful attempt to detect and quantify the change of FRET signals in A549 cells via three methods to monitor the cellular uptake of nanoprobes and intracellular drug molecule release intuitively. As we proposed here, the combination of free DOX and the self-assembling peptide could achieve the synergistic anticancer efficacy. The multifunctional PEG-Pep-TPE/DOX nanoparticles may provide a new opportunity for combination cancer therapy and real-time detection of the drug release from stimuli-responsive nanomedicine.